Early and continuous neurologic improvements after intravenous thrombolysis are strong predictors of favorable long-term outcomes in acute ischemic stroke. - Yeo, L; Paliwal, P; Teoh, H; Seet, R; Chan, B; Wakerley, B; Liang, S; Rathakrishnan, R; Chong, V; Ting, E; Sharma, V (2013)
BACKGROUND: Intravenously administered tissue plasminogen activator (IV tPA) remains the only approved therapeutic agent for arterial recanalization in acute ischemic stroke (AIS). Considerable proportion of AIS patients demonstrate changes in their neurologic status within the first 24 hours of intravenous thrombolysis with IV tPA. However, there are little available data on the course of clinical recovery in subacute 2- to 24-hour window and its impact. We evaluated whether neurologic improvement at 2 and 24 hours after IV tPA bolus can predict functional outcomes in AIS patients at 3 months. METHODS: Data for consecutive AIS patients treated with IV tPA within 4.5 hours of symptom onset during 2007-2011 were prospectively entered in our thrombolyzed registry. National Institutes of Health Stroke Scale (NIHSS) scores were recorded before IV tPA bolus, at 2 and 24 hours. Early neurologic improvement (ENI) at 2 hours was defined as a reduction in NIHSS score by 10 or more points from baseline or an absolute score of 4 or less points at 2 hours. Continuous neurologic improvement (CNI) was defined as a reduction of NIHSS score by 8 or more points between 2 and 24 hours or an absolute score of 4 or less points at 24 hours. Favorable functional outcomes at 3 months were determined by modified Rankin Scale (mRS) score of 0-1. RESULTS: Of 2460 AIS patients admitted during the study period, 263 (10.7%) received IV tPA within the time window; median age was 64 years (range 19-92), with 63.9% being men, a median NIHSS score of 17 points (range 5-35), and a median onset-to-treatment time of 145 minutes (range 57-270). Overall, 130 (49.4%) thrombolyzed patients achieved an mRS score of 0-1 at 3 months. The female gender, age, and baseline NIHSS score were found to be significantly associated with CNI on univariate analysis. On multivariate analysis, NIHSS score at onset and female gender (odds ratio [OR]: 2.218, 95% confidence interval [CI]: 1.140-4.285; P=.024) were found to be independent predictors of CNI. Factors associated with favorable outcomes at 3 months on univariate analysis were younger age, female gender, hypertension, NIHSS score at onset, recanalization on transcranial Doppler (TCD) monitoring or repeat computed tomography (CT) angiography, ENI at 2 hours, and CNI. On multivariate analysis, NIHSS score at onset (OR per 1-point increase: .835, 95% CI: .751-.929, P<.001), 2-hour TCD recanalization (OR: 3.048, 95% CI: 1.537-6.046; P=.001), 24-hour CT angiographic recanalization (OR: 4.329, 95% CI: 2.382-9.974; P=.001), ENI at 2 hours (OR: 2.536, 95% CI: 1.321-5.102; P=.004), and CNI (OR: 7.253, 95% CI: 3.682-15.115; P<.001) were independent predictors of favorable outcomes at 3 months. CONCLUSIONS: Women are twice as likely to have CNI from the 2- to 24-hour period after IV tPA. ENI and CNI within the first 24 hours are strong predictors of favorable functional outcomes in thrombolyzed AIS patients.